Hypertension Risk in Young Women With Polycystic Ovary Syndrome: A Nationwide Population-Based Cohort Study - Wu, Cheng-Hsuan; Chiu, Lu-Ting; Chang, Yu-Jun; Lee, Chun-I; Lee, Maw-Sheng; Lee, Tsung-Hsien; Wei, James Cheng-Chung (Frontiers in Medicine, 2020)
Objective: A number of publications have assessed the prevalence of hypertension in polycystic ovary syndrome (PCOS) patients with inconclusive results. Since in general populations the occurrence of hypertension is related to age and comorbidities, we investigated the incidence rate and hazard ratios (HRs) of hypertension between healthy subjects and young women with PCOS as well as comorbidities. Methods: We conducted a population-based retrospective cohort study by using the National Health Insurance Research Database in Taiwan. The cohort included women with the diagnosis of PCOS between 2000 and 2012. Those without PCOS were selected as the control group at a ratio of 4:1 by an age-matched systematic random-sampling method. Cox proportional hazard regression analysis was used to determine the effects of PCOS on the risks of developing hypertension. Stratification analysis was performed to elucidate the interaction among PCOS and the comorbidities, which affect the incidence of hypertension. Results: The PCOS cohort consisted of 20,652 patients with PCOS and the comparison cohort consisted of 82,608 matched patients without PCOS. There was no difference in the distribution of age between the PCOS cohort and the comparison cohort (29.1 ± 6.8 vs. 29.0 ± 6.5, p = 0.32). The incidence rates of hypertension were 7.85 and 4.23 per 1000 person-years in the PCOS and comparison groups, respectively. A statistically significant higher risk of hypertension was found in the PCOS cohort (adjusted HR = 1.62, 95% confidence interval = 1.48 - 1.76) than in the comparison cohort. After a joint analysis of comorbidities, the adjusted HR of hypertension was 9.44 (95% confidence interval = 7.27 - 12.24) for PCOS patients with comorbidities of diabetes mellitus (DM) and hyperlipidemia compared with women with neither PCOS nor DM and hyperlipidemia. Conclusion: The risk of developing hypertension in young women with PCOS was higher than in controls in this cohort study. The comorbidities of DM and hyperlipidemia could interact with PCOS patients and further increase the risk of hypertension. An earlier screening for hypertension and comorbidities in patients with PCOS may be warranted, even in young women.